Contraceptive use among women living with HIV enrolled for the birth cohort study - Changata, Youlandar (Midlands State University, 2019)
The study focused on contraceptive use among women living with HIV enrolled for the birth cohort study. Also core to the study was an analysis of the factors that have facilitated the use of contraception amongst women living with HIV. There is a knowledge gap and limited research and on contraception use among women living with HIV. The study was guided by a conceptual framework that shows the various factors that could predict the utilization of contraception. The research adopted a quantitative and qualitative approach and the target population for the study was 1111 women from four clinics, Rujeko, Kwadzana, Budiriro, and Glenview enrolled for the study. Amongst the women 571 were positive. The research was also extended to key service provider in order to hear their views. Purposive sampling was used in order to select relevant respondents for the qualitative part of the study and thematic analysis was used to analyse the data. For the quantitative part of the study participants` data was obtained from University of Zimbabwe immunology department and it was analysed through excel and SPSS. The findings from the study demonstrated that Contraception use is generally high in Zimbabwe. Women living with HIV and women without HIV have similar patterns in contraception use and both use oral contraception pills mostly. The HIV positive women seem to be using condoms more than their counterparts. There is a knowledge gap however on hormonal contraceptive. Recommendations were made to the ministry of health to enhance family planning services so that they offer extensive education on use of various contraception. Midlands State University to take the opportunity to use the research finding of contraception use for its student family planning clinic through education, posters and online sites.Invovlment of man in family planning to support women living with HIV and clear misconceptions and myths. Lastly for service provider to inform the women of the combination of using hormonal family planning when on ART.